Pengaruh Variasi Persentase Hardener pada Campuran Clear Coat Terhadap Kekerasan Cat Pada Pengecatan Body Kendaraan - Hermon Latumaerissa; Nevada. J.M Nanulaita; Roy R Lekatompessy; Laily Ulfiyah (Jurusan Teknik Mesin, 2023)
Painting is a process of applying paint in liquid form to an object, to create a thin layer which then creates a hard layer or layer of paint. The function of painting itself is to give a layer to an object so that the object's lifespan can be longer. Attachment of paint to the surface can be done in many ways, wiping, smearing, brushing, spraying, dipping or in other ways. Attachment of paint by spraying is the paint attachment that is most often found in automotive painting workshops. Apart from that, attaching paint by spraying is easier in adjusting the area where painting will be carried out, the results are also good if done correctly. The quality of good painting results is influenced by many factors such as skills, materials used, etc., while determining good painting results is based on several factors, such as surface roughness, gloss power, etc. The hardness of the painting results is also greatly influenced by the percentage of hardener mixture in the paint mixture. The paint in question here is color paint (top coat). This research is to determine the best percentage of clearcoat in the painting process by testing the hardness of the painting results. The results obtained by varying the percentage of the mixture in the best clearcoat are in the percentage variations of 100 (Base): 55 (Hardener) + Thiner or Solvent (10% of Base) is 83.49 H, 100 (Base): 55 (Hardener) + Thiner or Solven (10% of Base) is 82.99 H, 100 (Base) : 45 (Hardener) + Thiner or Solven (10% from Base) is 82.51 H and the lowest is the variation 100 (Base): 60 (Hardener) + Thiner or Solvent (10% of Base) namely 79.57 H. Keywords: Painting, Clearcoat, Hardener and Paint hardness